2002
DOI: 10.1152/ajpgi.00441.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver myofibroblasts and hepatic stellate cells differ in CD95-mediated apoptosis and response to TNF-α

Abstract: Hepatic stellate cells (HSC), particularly activated HSC, are thought to be the principle matrix-producing cell of the diseased liver. However, other cell types of the fibroblast lineage, especially the rat liver myofibroblasts (rMF), also have fibrogenic potential. A major difference between the two cell types is the different life span under culture conditions. Although nearly no spontaneous apoptosis could be shown in rMF cultures, 18 ± 2% of the activated HSC ( day 7) were apoptotic. Compared with activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…The former cells lack growth ability and spontaneously undergo activation (induction of SMA expression) and, as recently described, to terminal diVerentiation characterized by expression of a large panel of late vascular smooth muscle cell markers (Wirz et al 2008) and manifested by the spontaneous Fasmediated apoptosis . Importantly, these same investigators have (Ogawa et al 2007;Saile et al 2002;Dudas et al 2003), clearly demonstrated that the minor cell population, MFs, but not aHSCs, have replicative activity (Table 2). At 7 days in culture aHSC expressed Desmin, P100, and Alpha-2-Macroglobulin, MF expressed Fibulin-2, but not P100, and Alpha-2 Macroglobulin (Knittel et al 1999a;Ogawa et al 2007, Table 2).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The former cells lack growth ability and spontaneously undergo activation (induction of SMA expression) and, as recently described, to terminal diVerentiation characterized by expression of a large panel of late vascular smooth muscle cell markers (Wirz et al 2008) and manifested by the spontaneous Fasmediated apoptosis . Importantly, these same investigators have (Ogawa et al 2007;Saile et al 2002;Dudas et al 2003), clearly demonstrated that the minor cell population, MFs, but not aHSCs, have replicative activity (Table 2). At 7 days in culture aHSC expressed Desmin, P100, and Alpha-2-Macroglobulin, MF expressed Fibulin-2, but not P100, and Alpha-2 Macroglobulin (Knittel et al 1999a;Ogawa et al 2007, Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, in vitro studies have classiWed SMA/ Fibulin-2/IL-6 positive cells as MF (Knittel et al 1999a;Ramadori and Saile 2002;Saile et al 2002). Functional in vitro studies suggest that cultured rat HSC and MF diVer not only in expressing diVerent markers, but also in expressing diVerent cytokines and growth factors (Schirmacher et al 1992;Tiggelman et al 1995;Knittel et al 1999a), as well as their diVerent responses to various cytokines and growth factors (Tiggelman et al 1995;Saile et al 2002Saile et al , 2004. Moreover, they also diVer in apoptotic and proliferation characteristics, and in cell cycle regulation Dudas et al 2003;Ogawa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we cannot explore more deeply the Axl decrease in HSC/MFB because of their short half-life in culture after transformation and the parallel rapid outgrowth of desmin-negative fibroblasts in the dish as previously reported. 38 Nevertheless, Axl decrease is probably not due to a downregulation by Gas6, because it was also observed in cells cultured in the absence of vitamin K, a situation that prevents binding of Gas6 to its receptor.…”
Section: Discussionmentioning
confidence: 93%
“…The prominent accumulation of portal myofibroblasts over myofibrolastic HSCs, at least in biliary fibrosis, is in keeping with comparative studies of the two cell types in culture, showing that portal myofibroblasts are much more proliferative, whereas myofibrolastic HSCs are more susceptible to spontaneous and provoked apoptosis. 38,39 In the model of arterial liver ischemia, the regression of injury was accompanied by a stabilization of fibrosis and a regression of a-SMA-immunoreactive cells, which were undetectable after 6 weeks, except for the cells lining newly formed vessels. As we previously showed that VEGF expression was induced both in cholangiocytes and in periportal hepatocytes in the model of arterial liver ischemia, we may anticipate that Figure 7 a-SMA and desmin expression profiles according to fibrosis evolution in ischemia-induced injury.…”
Section: Discussionmentioning
confidence: 99%